1996
DOI: 10.2134/agronj1996.00021962008800010022x
|View full text |Cite
|
Sign up to set email alerts
|

Performance of ‘Grasslands Puna’ Chicory at Different Management Levels

Abstract: ‘Grasslands Puna’ chicory (Cichorium intybus L.) is a perennial taprooted herb that shows potential to produce high yields of palatable forage for ruminants. Our objective was to determine management effects on herbage production and quality, and stand persistence. Chicory and ‘Pennlate’ orchardgrass (Dactylis glomerata L.) were established on Hagerstown silt loam (fine, mixed, mesic Typic Hapludalf) soil at Rock Springs, PA. Treatments were intensive, moderate, and lenient management, corresponding to 25‐, 37… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
47
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(55 citation statements)
references
References 9 publications
(9 reference statements)
6
47
2
Order By: Relevance
“…The current study's findings on chicory protein, neutral detergent fiber, tannin concentrations and seasonal growth patterns, are consistent with the literature indicating this species can provide adequate quality forage for deer pasture throughout the summer (CP [35], NDF [36], condensed tannins [37,38]. The decline in chicory NDF from an initial high in July, into August and September, led to greater digestibility in this species compared to the other forages in late summer and fall.…”
Section: Forage Qualitysupporting
confidence: 89%
“…The current study's findings on chicory protein, neutral detergent fiber, tannin concentrations and seasonal growth patterns, are consistent with the literature indicating this species can provide adequate quality forage for deer pasture throughout the summer (CP [35], NDF [36], condensed tannins [37,38]. The decline in chicory NDF from an initial high in July, into August and September, led to greater digestibility in this species compared to the other forages in late summer and fall.…”
Section: Forage Qualitysupporting
confidence: 89%
“…Recent studies have identified a number of dicotyledonous plant species with a high forage productivity when grown in complex forage communities [15, 16]. For example, chicory ( Cichorium intybus L.) is a perennial deep-rooting, broad-leafed forage forb documented as a valuable forage species with high productivity and high feed value [1719]. Plantain ( Plantago lanceolate L.) is another forage forb characterized by deep roots, drought resistance and a wide distribution in temperate grasslands [20, 21].…”
Section: Introductionmentioning
confidence: 99%
“…Several experiments have shown that chicory has a high content of sodium, zinc, copper, iron, calcium, magnesium and sulphur compared to ryegrass and lucerne Crush and Evans, 1990;Jung et al, 1996). Thus, chicory in a grass mixture may have the potential to improve the supply of microminerals in the diet.…”
Section: Introductionmentioning
confidence: 99%